2018
DOI: 10.1007/s00125-018-4669-0
|View full text |Cite
|
Sign up to set email alerts
|

The actions of SGLT2 inhibitors on metabolism, renal function and blood pressure

Abstract: Inhibition of the sodium-glucose cotransporter (SGLT) 2 in the proximal tubule of the kidney has a broad range of effects on renal function and plasma volume homeostasis, as well as on adiposity and energy metabolism across the entire body. SGLT2 inhibitors are chiefly used in type 2 diabetes for glucose control, achieving reductions in HbA of 7-10 mmol/mol (0.6-0.9%) when compared with placebo. This glucose-lowering activity is proportional to the ambient glucose concentration and glomerular filtration of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
183
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(212 citation statements)
references
References 62 publications
(97 reference statements)
4
183
0
14
Order By: Relevance
“…The glucosuric effects of SGLT‐2is promote reductions in body weight and body fat . Sodium reabsorption is decreased with SGLT‐2is, leading to a transient increase in sodium excretion (natriuresis) and an associated antihypertensive effect …”
Section: Mechanism Of Glyaemic Control With Sglt‐2 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glucosuric effects of SGLT‐2is promote reductions in body weight and body fat . Sodium reabsorption is decreased with SGLT‐2is, leading to a transient increase in sodium excretion (natriuresis) and an associated antihypertensive effect …”
Section: Mechanism Of Glyaemic Control With Sglt‐2 Inhibitorsmentioning
confidence: 99%
“…Intravascular volume reductions are initially caused by the natriuretic effects of SGLT‐2is, which result from reduced sodium reabsorption in the proximal tubule, and may be further increased by treatment combined with diuretic therapy . However, natriuresis with SGLT‐2is is thought to be transient, as sodium excretion has been shown to return to baseline levels within days of initiating SGLT‐2i therapy, and is therefore unlikely to be the sole underlying mechanism . It is hypothesized that the osmotic diuretic effects of glucosuria, combined with increased sodium flow through the proximal tubule, lead to homeostatic changes that include reductions in steady‐state plasma volume, which probably contribute to the antihypertensive effects of SGLT‐2is …”
Section: Mechanisms Of CV and Renal Protection With Sglt‐2 Inhibitorsmentioning
confidence: 99%
“…Sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors suppress glucose reabsorption in the kidney to increase urinary glucose excretion, resulting in reductions in fasting and postprandial glucose. These improvements are coupled with changes in adiposity, substrate utilization, lipolysis, hormone secretion and central regulation of appetite . SGLT2 inhibitors also appear to have beneficial effects with regard to renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with SGLT2 inhibitors leads to a reduction in the insulin:glucagon ratio and increases hepatic glucose production by gluconeogenesis . In a recent study, administration of SGLT2 inhibitors alleviated glucose toxicity and improved peripheral insulin sensitivity, but increased glucose production in the liver by increasing glucagon levels . Recent studies also showed that NAD‐dependent deacetylase sirtuin‐1 (SIRT1) interacts with and deacetylates peroxisome proliferative activated receptor‐gamma co‐activator 1α (PGC‐1α or PPARGC1), leading to induction of gluconeogenic gene expression in the liver .…”
Section: Introductionmentioning
confidence: 99%